Improving Infrastructure in Child-Friendly Public Spaces RW.10 Pekalipan Village, Cirebon City - Bakhri, Syaeful; Alamsyah, Muhammad Fakhri; Pradini, Anez Yuniar (Society : Jurnal Pengabdian Masyarakat, 2025)
This study evaluates the availability and condition of child-friendly infrastructure in RW.10 Pekalipan Village, Cirebon City, as part of the implementation of the Child-Friendly City Program (KLA).  The method used is Participatory Action Research (PAR) by involving the community, village officials, and academics in the process of identifying issues, mapping potential, and implementing infrastructure development actions. Data was collected through observation, interviews, and document studies.  The results of the study show that the child-friendly infrastructure in Pekalipan Village is quite adequate, including health facilities, education, green open spaces, and playgrounds. The local government has made efforts to improve public facilities and encourage community participation in development planning and evaluation. However, there are still challenges such as equitable distribution of facilities, the need for renovation, and the need to increase children's participation in the development process.  This research emphasizes the importance of cross-sector collaboration and collaborative governance models to optimize KLA development. The resulting policy implications include the need to strengthen regulations, routine maintenance of facilities, and the active involvement of children and the community. These findings are in line with a recent study that highlights the importance of continuous evaluation and innovation in the development of child-friendly cities in Indonesia.